Modelling the hydrology of watershed by using HEC-HMS - MAKKENA JYOTHI; Er. Vishnu B (Guide) (Tavanur 2016 DEPARTMENT OF IRRIGATION AND DRAINAGE ENGINEERING)
HEC-HMS uses separate mathematical models to represent each component of the runoff process, like models to compute runoff volume, models to compute direct runoff and base flow.thuthapuzha subbasin of bharathapuzha
Modelling the hydrology of watershed by using HEC-HMS